PENGARUH FAKTOR LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI KELAS XI DI SMK MUHAMMADIYAH 2 PEKANBARU - Sri Rahmadani; Gusnardi '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study was a difference between expectations and reality occurred at class XI Accounting in SMK Muhammdiyah 2 Pekanbaru. There is 34,95% students have value under minimum completeness criteria value. The purpose of this study was to determine and analyze how the effect of family environment to learning achievement of Accounting subject at class XI in SMK Muhammadiyah 2 Pekanbaru. The population of this study all student who have mid test value under minimum completeness criteria value as many as 43 students. Data collection methods used were questionnaires and documentation. Method of data analysis are descriptive analysis and regressions analysis. Based on the result of analysis data is concluded has positive effect and significant among family environment (X) on learning achievement (Y). Based on R square table showed 0,167 it means independent variable used in this study has effect on dependent variable as many as 16,7%. Therefore, ability independent variable for influence dependent variable is weak. This is due to many another variables which influence dependent variable.Key Words: Family Environment, Learning Achievement